Synthesis and Characterization of Some Oxo-cations Complexes with Heterocyclic Thioamide Ligand - Pandey, R.N.; Shahi, Kalpana (Asian Journal of Chemistry, 2011)
Mono nuclear oxo-cation complexes with 1,2,4-triazole-3(s) thione have been prepared and characterized on the basis of elemental analysis, molar conductance, spectral (IR, electronic) studies and magnetic susceptibility measurements. The ligand behaves as mononegative bidentate ligand having bonding through deprotonated imino nitrogen and thiocarbonyl sulphur. IR spectra suggest existence of cis-dioxo structure of VO2+, MoO22+ and WO22+ species, which forces the ligand to coordinate in a non-planar fashion and allow better O(pπ) - M(dπ) bonding than linear arrangement would allow in octahedral geometry.